Unraveling the Immunopathogenesis and Genetic Variants in Vasculitis Toward Development of Personalized Medicine - Yap, Bryan Ju Min; Lai-Foenander, Ashley Sean; Goh, Bey Hing; Ong, Yong Sze; Duangjai, Acharaporn; Saokaew, Surasak; Chua, Caroline Lin Lin; Phisalprapa, Pochamana; Yap, Wei Hsum (Frontiers in Cardiovascular Medicine, 2021)
Leukocytoclastic vasculitis (LCV) is a systemic autoimmune disease characterized by the inflammation of the vascular endothelium. Cutaneous small vessel vasculitis (CSVV) and anti-neutrophil cytoplasmic antibodies (ANCA)-associated vasculitis (AAV) are two examples of LCV. Advancements in genomic technologies have identified risk haplotypes, genetic variants, susceptibility loci and pathways that are associated with vasculitis immunopathogenesis. The discovery of these genetic factors and their corresponding cellular signalling aberrations have enabled the development and use of novel therapeutic strategies for vasculitis. Personalized medicine aims to provide targeted therapies to individuals who show poor response to conventional interventions. For example, monoclonal antibody therapies have shown remarkable efficacy in achieving disease remission. Here, we discuss pathways involved in disease pathogenesis and the underlying genetic associations in different populations worldwide. Understanding the immunopathogenic pathways in vasculitis and identifying associated genetic variations will facilitate the development of novel and targeted personalized therapies for patients.